2013
DOI: 10.1111/asj.12083
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield, gross composition and fatty acid profile of dual‐purpose Aosta Red Pied cows fed separate concentrate‐forage versus total mixed ration

Abstract: This study was designed to evaluate the effects of two feeding methods on milk yield, composition and fatty acid (FA) profile obtained from dual-purpose cattle. Twenty-four Aosta Red Pied cows beyond peak of lactation were assigned to two groups and fed hay and concentrates in the proportions 0.69 and 0.31 on a dry matter basis for 10 weeks. Concentrates were offered separately from forages 6 times a day (separate ration, SR) or as a total mixed ration (TMR). The feeding method did not significantly influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…The content of groups of FA in milk of Aosta Red Pied breed was in general lower than that of breeds investigated in the present study. Calculations from Renna et al (2014) for groups of FA were however conducted differently than calculations from Niero et al (2016) and because of major differences, it appears that they were not comparable with values of the present report.…”
Section: Effects Of Parity Number Lactation Stage and Seasoncontrasting
confidence: 90%
See 1 more Smart Citation
“…The content of groups of FA in milk of Aosta Red Pied breed was in general lower than that of breeds investigated in the present study. Calculations from Renna et al (2014) for groups of FA were however conducted differently than calculations from Niero et al (2016) and because of major differences, it appears that they were not comparable with values of the present report.…”
Section: Effects Of Parity Number Lactation Stage and Seasoncontrasting
confidence: 90%
“…Both the latter breeds were found to have greater C14:0 (12.29 and 12.77%, respectively), C:18:0 (11.32 and 11.33%) and C:18:1 (23.64 and 23.44%) and lower levels of C16:0 (31.26 and 30.61%) compared with breeds considered in the present study. Other comparable data comes from Niero et al (2016) and Renna et al (2014) who investigated milk yield, milk quality and FA composition of Burlina, a typical local cattle breed of northeast Italy, and Aosta Red Pied breed, typical of northwest Italy. Milk from Burlina and Aosta Red Pied cows exhibited lower content of C14:0 (11.11 and 10.18%, respectively), C16:0 (29.16 and 28.17%) and C:18:0 (7.95 and 6.58%) compared with Holstein-Friesian, Brown Swiss, Simmental and Alpine Grey cows studied in the present work.…”
Section: Effects Of Parity Number Lactation Stage and Seasonmentioning
confidence: 99%
“…In terms of milk yield and milk gross composition, results of the present study are comparable to those reported by Battaglini et al (2009) and Renna et al (2014), who studied milk yield and milk composition of Aosta cows. The contents of fat, protein and CN in the ARP milk were lower than those found in pure dairy breeds including Holstein-Friesian, Brown Swiss and Simmental cows (Penasa et al 2014).…”
Section: Variation and Correlations Of Milk Quality And Technologicalsupporting
confidence: 90%
“…In the lowland, milk fat content was unexpectedly low compared to Renna et al (2014). However, to our knowledge, previous measurements only featured hay.…”
Section: Effects Of Alpine Grazingmentioning
confidence: 58%